Lipidic matrices of Essential oils: A developing strategy to preserve their biological activity and improve their stability (2020)
ABSTRACT: Essential oils (EOs) have garnered the attention of many researchers in recent years due to their potential as complementary and alternative antioxidants, anti-inflammatory, anticancer, antibacterial, antifungal, and antiviral activities. However, their utilization is very limited due to low water solubility, evaporation, and instability to factors such as light, humidity and oxygen. This study explored the potential structuring of 20 selective EOs into lipophilic matrixes with seven different emulsifiers and determined the mechanism involved in such process. The composite Hansen parameters along with the gelling capacity, volatile retention, and oil binding ability were evaluated and analyzed by multivariate analysis. The structuring capacity mainly depended on the cohesive forces (mainly hydrogen bond interactions) of the emulsifier, which in turn was related to the radius of solubility of the EOs (r>0.895). Matrixes produced with natural waxes showed the largest strength (~100%), oil binding (>97%) and volatile retention (~100%), whereas stearic acid showed the lowest values (25-30%). EOs from origanum, clove, cinnamon, and basil having large hydrogen bond forces developed the strongest lipidic matrixes. This phenomenon was attributed to the presence of an exocyclic oxygen coupled with adjacent Π electrons. EOs structuring was achieved by forming colloidal lipidic matrixes, especially with waxy emulsifiers, whereas polymeric materials only caused a partial swelling.